Design and performance estimate of a telescope dedicated to solar system planet imagery - Weerapot Wanajaroen (2018)
© 2018 SPIE. The observations of the solar system Jovian planets performed by ground-based medium size telescopes can provide an efficient support to the space missions by performing observations of the planet atmospheres. In particular, ground-based medium size telescopes are able to provide high resolution images close to the diffraction limit of giant planets while observing through the Earth atmosphere by using some Lucky Imaging processing. These observations of the Jovian planet atmospheres ideally require i) an instrument with a high angular resolution close to the diffraction limit and ii) a high contrast, especially for the low and medium spatial frequencies that corresponds to the turbulence areas inside the atmosphere clouds bands. We thus decided to design one telescope that shall provide diffraction limited images (without the contribution of the atmosphere) over a circular Field of View (FOV) of diameter equal to 2 arcminutes. This, over the photometric spectral band V, R and I of the Johnson-Cousin photometric. In this paper, we present the design and the performance of a Ritchey-Chretien telescope dedicated to solar system planet imagery with a linear central obscuration lower than 0.15 and an active system to correct the low frequency distortions of the wavefront before each observation. First, we describe the optical design, then we establish the image quality budget. Finally we show that the stray light signal induced by the moon light scattering is negligible during the observations of Jupiter.